THE IMPLEMENTATION OF COOPERATIVE LEARNING IN TEACHING DESCRIPTIVE TEXT - Rahmah, Ima Siti (Politeknik Siber Cerdika Internasional, 2024)
The present research reported the use of cooperative learning model in improving student’s writing comprehension. The research was conducted to find out whether or not cooperative learning improved student’s writing comprehension, and to find out student’s perception toward the implementation of cooperative learning model. The design employed in this research was the Case Research. The research was conducted at seventh grade of E which involved twelve female students in it, and it was conducted at Modern Islamic Boarding School Nurul Fajri located in Weragati Palasah Majalengka. The observation checklist, student’s questionnaire, interview sheet and document analyses were implemented as instruments to collect the data. The findings of the research showed that cooperative learning model (Think Pair Share TPS) improved the student’s comprehension in writing descriptive text. Except that, the findings also showed that the students gave positive responses since they started that cooperative learning method were fun and helped them in understanding descriptive text and they wanted to know more about it. And it is shown in the findings that the implementation of cooperative learning that implemented by the teacher to seventh grade with using the Think Pair Share (TPS) technique run well.